Análisis del impacto socio-económico de las remesas del exterior en el desarrollo empresarial en la zona sur de Quito. Período 2004-2010 - Nogales Paucar, Geovanna Alexandra (2010)
This paper aims to examine recent trends in remittances in southern Quito sector evaluate the economic and social importance of these resources in the development of research, analyzing the socio demographic characteristics of the population that remittances and major obstacles in the operation of remittances and evaluate their economic and productive potential in southern Quito sector.